Grade five liver laceration following cardiopulmonary resuscitation: a case report - Mohammad Ashraf Azimi; Rasul Nikdel; Seyed Hassan Seyed Sharifi (Tehran University Medical Journal, 2024)
Background: Cardiopulmonary resuscitation (CPR) is a potentially life-saving treatment for cardiac arrest but puts the subject at risk for iatrogenic skeletal and soft tissue injuries including the liver. In this study, an elderly patient with grade 5 liver rupture after cardiopulmonary resuscitation following laparotomy is reported.